Negotiating individuality and collectivity in community music. A qualitative case study. (September 2019) - Schiavio, Andrea; van der Schyff, Dylan; Gande, Andrea; Kruse-Weber, Silke
In this paper, we report on a qualitative study based on the "Meet4Music" (M4M) project recently developed at the University of Music and Performing Arts Graz, Austria. M4M is a low-threshold community-based program where participatory sessions dedicated to different artistic activities are freely offered to people from different social and cultural backgrounds. Our study explores how M4M promotes self-expression, creativity, social understanding, and artistic development through a number of interviews that we collected with the "facilitators"—those who help guide the heterogeneous ensemble of participants without being committed to a fixed and pre-defined teaching content. Our data focus on three aspects of M4M: "mutual collaborations, " "non-verbal communication, " and "sense of togetherness." Taking the "enactive" approach to cognition as a theoretical background, we argue that M4M helps to promote a sense of community that goes beyond the distinction between "individuality" and "collectivity." M4M encourages participants to meaningfully engage in collective forms of artistic activities, and develop new perspectives on their cultural identities that can play a key role for their flourishing as musical beings. In conclusion, we briefly consider possibilities for future research and practice.